Effect of Access to Workplace Supports for Breastfeeding Among Formally Employed Mothers in Kenya. (7th June 2021) - Ickes, Scott; Kinyua, Joyceline; Adams, Joshua; Denno, Donna; Myhre, Jennifer; Ithondeka, Angeline; Iannotti, Lora; Farquhar, Carey; Singa, Benson; Walson, Judd; Nduati, Ruth
Abstract: Objectives: We evaluated the availability of workplace breastfeeding (BF) supports, and the associations between these supports and BF practices among formally employed mothers in Kenya – where many women work in horticulture farms and legislation requiring workplace BF supports is being implemented. We hypothesized that the availability of supports would be associated with a higher prevalence and greater odds of exclusive breastfeeding (EBF). Methods: We conducted repeated cross-sectional surveys among formally employed mothers at 1–4 days, 6 weeks, 14 weeks, and 36 weeks (to estimate 24 weeks) postpartum at 3 health facilities in Naivasha from Sept. 2018 to Oct. 2019, 13 months after the 2017 Kenyan Health Act, which requires workplace BF support, was passed. We evaluated the associations of workplace BF supports with EBF practices using tests of proportions and adjusted logistic regression. Results: Among formally employed mothers (n = 564), reported workplace supports included on-site housing (16.8%), on-site daycare (9.4%), and private lactation spaces (2.8%). Mothers who used workplace on-site childcare were more likely to practice EBF than mothers who used community- or home-based childcare at both 6 weeks (95.7% versus 82.4%, p = 0.030) and 14 weeks (60.6% versus 22.2%, p < 0.001; [aOR (95% CI) = 5.11 (2.3, 11.7)]. Likewise, mothers who visited daycares at or near workplaces were more likely to practice EBF (70.0%) compared to those who did not visit a daycare (34.7%, p = 0.005) at 14-weeks. Among all mothers, 84.6% with access to workplace private lactation spaces practiced EBF, compared to 55.6% without such spaces, p = 0.037. Mothers who live in on-site housing were twice as likely [aOR (95% CI) = 2.06 (1.25, 3.41)] to practice EBF compared to those without access to on-site housing. Conclusions: Formally employed mothers in Kenya who used on-site childcare, lived in on-site housing, and had access to private workplace lactation rooms are more likely to practice EBF than mothers who lack these supports, while the use of community-based childcare in this context is associated with a lower prevalence of EBF. As the Kenya Health Act is implemented, provision of these supports and strategies to help women visit their children in daycare can enable EBF among employed mothers. Funding Sources: NIH Fogarty International Center.